2015
DOI: 10.1016/j.ifacol.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory control for underbalanced drilling operations

Abstract: Good flow and pressure control is essential for successful Underbalanced Drilling (UBD) operations. This work evaluates the use of Model Predictive Control (MPC) for integrated control of well conditions and the topside separation system during UBD. The downhole well pressure, separator liquid levels, and the separator pressure are controlled by manipulation of the rig pump, the choke, and the separator valves. The control system adheres to downhole and topside constraints. These constraints include pore and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The essential time scale associated to these dynamics can be in the range of tens of seconds, or even minutes in the case of gas influx into the wellbore. Not only can such dynamics deteriorate the control performance, but they can also cause instability (Pedersen et al 2015), if not accounted for during the controller design stage;…”
Section: Introductionmentioning
confidence: 99%
“…The essential time scale associated to these dynamics can be in the range of tens of seconds, or even minutes in the case of gas influx into the wellbore. Not only can such dynamics deteriorate the control performance, but they can also cause instability (Pedersen et al 2015), if not accounted for during the controller design stage;…”
Section: Introductionmentioning
confidence: 99%
“…The reasonable transmission of UBD data is well-known to be problematic for mud-pulse telemetry (MPT) as the highly constrainable fluid for drilling used in UBD causes a dramatic increase in the attenuation of the MPT signal. 16 The ability to make sounds for judgment is very necessary to succeed in the implementation of UBD technology. Because of the complex nature of the implementation of the telemetry method, a closed mathematical expression is not feasible.…”
Section: F I G U R E 1 Under-balanced Drilling Drilling Processmentioning
confidence: 99%
“…Today telecommunications are primarily preferred for UBD operations with electromagnetic, 15 acoustic, and connectors. The reasonable transmission of UBD data is well‐known to be problematic for mud‐pulse telemetry (MPT) as the highly constrainable fluid for drilling used in UBD causes a dramatic increase in the attenuation of the MPT signal 16 …”
Section: Introduction and Background Important Of The Policiesmentioning
confidence: 99%
“…Model identification techniques were used to obtain 1st-order delay models for control of UBO using MPC by Pedersen and Godhavn (2013), with extensions in Pedersen et al (2015). This is similar to the technique used in (Nygaard et al, 2007b) where a NMPC controller was designed based on identified time constants.…”
Section: Ode-models From Identification Techniquesmentioning
confidence: 99%